Teonim Mori Keraéng dan Signifikansinya Terhadap Eko-pastoral Gereja - Juhani, Sefrianus; Jόzef Trzebuniak (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2025)
This article examines the theonym Mori Keraéng as a theological foundation for eco-pastoral practices in the Catholic Church, particularly in the context of indigenous Manggarai cosmology. It responds to the need for contextual theological models that integrate local wisdom with ecological responsibility. The study employs Martin Heidegger’s phenomenological methodology, which emphasizes allowing phenomena to disclose themselves and describing what appears without distortion. Fieldwork was conducted in three districts of Manggarai: East Manggarai, Manggarai, and West Manggarai by engaging local informants who have deep familiarity with the Mori Keraéng tradition. Informants were invited to share their lived understanding without interference, enabling the emergence of authentic cultural-theological insights. Findings reveal that Mori Keraéng is understood as a cosmic deity who not only creates but also sustains the Earth as a common household for all living beings. Nature is perceived as a medium of divine epiphany, revealing God's ongoing presence within creation. Furthermore, the relational dynamic within Mori Keraéng marked by mutual self-limitation and interpenetration (e.g., Father-Sky and Mother-Earth) offers a paradigm of intra-divine collaboration that serves as a model for ecological relationships among creatures. In conclusion, the indigenous concept of Mori Keraéng provides a rich theological resource for constructing a Catholic eco-theology grounded in local cosmological thought. It affirms the sacredness of creation and calls for a collaborative and respectful engagement with the natural world.